Deep frying : chemistry, nutrition, and practical applications - Erickson, Michael D. (AOCS Press, 2007)
Since the first edition of Deep Frying was published in 1996, there have been many changes to the U.S. Dietary Guidelines and nutritional labeling laws, and improvements in frying technology and practices have made a significant impact on the industry. This book will cover everything you need to know to create fat and oil ingredients that are nutritious, uniquely palatable and satisfying.
Keywords: Oils and fats, Edible.; Deep frying.; Unsaturated fatty acids in human nutrition.; Feeds -- Composition.; Food -- Composition.; elektronické knihy; electronic books